Influence of periodontitis on Th17/Treg percentages in patients with rheumatoid arthritis = Influencia de la periodontitis sobre los porcentajes de células Th17/Treg de pacientes con artritis reumatoide - Martínez Martínez, Rita Elizabeth
Th17/Treg cells and P. gingivalis have been implicated in rheumatoid arthritis (RA) and periodontitis (PE). The aim was to determine and compare Th17/Treg cells and the influence of P. gingivalis on this cell population in healthy subjects (HS) and patients with PE, RA, and PE/RA. The number of copies of P. gingivalis was performed by real-time PCR and flow cytometry was used to analyze Th17/Treg cells. In this study, PE in patients with RA increased the number of DNA copies of P. gingivalis, increasing the percentages of Th17 cells, as well as the number and regulation of Treg cells. Periodontitis influences the immune system, increasing the percentage of pro-inflammatory cells in patients with rheumatoid arthritis, which may could influence the inflammatory condition of this population.